Upaya Meningkatkan Pemahaman Qawaid Melalui Penggunaan Media Kartu Bagi Siswa Kelas VII MTsN 8 Kediri - Emmy Anisnaini (Institut Agama Islam Negeri Kediri, 2021)
Abstract: Language learning consist of teaching language rules and language skills wherever students are required to master both. Understanding and mastery of grammatical rules, such as nahwu and shorof are also very necessary in learning Arabic, both in formal and non-formal learning. In the implementation of learning Arabic, there are still problems like some students still find the difficulty of understanding the rules of the Arabic language. This is caused by several factors including the teacher’s methods and techniques in delivering the material that is less varied. In addition, student’s backgrounds are different so that not all off them have Arabic language competence. Likewise for learning Arabic in Qawaid material at MTsN 8 Kediri, especially for class VII-B. Based on the results of observations and pre-test results showedd that student learning outcomes in Qawaid learning were still very low, namely the majority of students scored below 50. This type of research used classroom action research (CAR). Data collection techniques used in the form of tests, observations and documentation. Analysis of the data used is a comparison between test. The number of subjects in this study were 33 subject. The results of this study indicated (1) The need for the use of various methods in order to improve student’s understanding of Arabic subject in general; (2) the word card method is one method that can improve student’s understanding of Qawaid in learning Arabic.Abstrak: Pembelajaran bahasa terdiri atas pengajaran kaidah bahasa dan keterampilan berbahasa dimana siswa dituntut untuk menguasai keduanya. Pemahaman dan penguasaan kaidah tata bahasa, seperti nahwu dan shorof juga sangat diperlukan dalam pembelajaran bahasa Arab baik dalam pembelajaran formal maupun non-formal. Dalam pelaksanaan pembelajaran bahasa Arab masih ditemui permasalahan di antaranya sebagian siswa masih merasa kesulitan dalam memahami kaidah bahasa Arab. Hal ini disebabkan oleh beberapa faktor di antaranya metode dan teknik guru dalam menyampaikan materi yang kurang variatif. Selain itu, latar belakang siswa berbeda-beda sehingga tidak semuanya memiliki kompetensi bahasa Arab. Begitu juga pada pembelajaraan bahasa Arab pada materi qawaid di MTsN 8 Kediri khususnya kelas VII-B. Berdasarkan hasil pengamatan dan hasil pre-test menunjukkan bahwa hasil belajar siswa pada pembelajaran qawaid masih sangat rendah yaitu mayoritas siswa mendapat nilai dibawah 50. Jenis penelitian menggunakan penelitian tindakan kelas (PTK). Teknik pengumpulan data yang digunakan berupa tes, observasi dan dokumentasi. Analisis data yang digunakan adalah perbandingan antar tes. Jumlah subjek dalam penelitian sebanyak 33 subjek. Hasil penelitian ini menunjukkan: 1. Perlunya penggunaan metode yang bervariasi agar dapat meingkatkan kemampuan pemahaman siswa terhadap qawaid dalam mata pelajaran bahasa Arab umumnya. 2. Metode kartu kata adalah salah satu metode yang dapat meingkatkan pemahaman siswa terhadap qawaid dalam pembelajaran bahasa Arab.